TERT and DNMT1 expression predict sensitivity to decitabine in gliomas - Park, Jongwhi; Sahm, Felix; Steffl, Bianca; Arrillaga-Romany, Isabel; Cahill, Daniel; Monje, Michelle; Herold-Mende, Christel; Wick, Wolfgang; Turcan, S̨evin (Neuro-Oncology, 2021)
Decitabine (DAC) is an FDA-approved DNA methyltransferase (DNMT) inhibitor that is used in the treatment of patients with myelodysplastic syndromes. Previously, we showed that DAC marks antitumor activity against gliomas with isocitrate dehydrogenase 1 (IDH1) mutations. Based on promising preclinical results, a clinical trial has been launched to determine the effect of DAC in IDH-mutant gliomas. The next step is to comprehensively assess the efficacy and potential determinants of response to DAC in malignant gliomas.The expression and activity of telomerase reverse transcriptase (TERT) and DNMT1 were manipulated in patient-derived IDH1-mutant and -wildtype glioma lines, followed by assessment of cell proliferation with DAC treatment alone or in combination with telomerase inhibitors. RNA sequencing, Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment, and correlation analysis were performed.IDH1-mutant glioma tumorspheres with hemizygous codeletion of chromosome arms 1p/19q were particularly sensitive to DAC and showed significant inhibition of DNA replication genes. Our transcriptome analysis revealed that DAC induced expression of cyclin-dependent kinase inhibitor 1A/p21 (CDKN1A), along with downregulation of TERT. These molecular changes were also observed following doxorubicin treatment, supporting the importance of DAC-induced DNA damage in contributing to this effect. We demonstrated that knockdown of p21 led to TERT upregulation. Strikingly, TERT overexpression increased DNMT1 levels and DAC sensitivity via a telomerase-independent mechanism. Furthermore, RNA inhibition (RNAi) targeting of DNMT1 abrogated DAC response in TERT-proficient glioma cells.DAC downregulates TERT through p21 induction. Our data point to TERT and DNMT1 levels as potential determinants of response to DAC treatment.
Gesehen am 28.07.2021
Advance access date 3 September 2020